SAUDI DELEGATION VISIT STRENGTHENS TIES WITH USM - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 19 May 2015 The ViceChancellor of Universiti Sains Malaysia (USM), Professor Dato' Dr. Omar Osman recently welcomed the delegation of the Saudi Arabian Embassy in a courtesy call at the Bilik Persidangan Canselori USM. Omar said, he was truly honoured in welcoming the delegates from the Saudi Arabian Embassy to establish collaborative opportunities and discuss various issues pertaining to Saudi students pursuing their education at USM.